2019
DOI: 10.17159/0379-4350/2019/v72a16
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of Dexamethasone and Fluoroquinolones; in vitro Study

Abstract: A precise, accurate and sensitive liquid chromatographic method is presented for the simultaneous analysis of moxifloxacin, levofloxacin, ciprofloxacin and dexamethasone in reference drugs, ophthalmic dosage form and in physiological fluids. Separation was achieved on a C 18 analytical column with acetonitrile-phosphate buffer (35:65 v/v) as mobile phase which was pumped isocratically at a flow rate of 1.0 mL min-1 and monitored at 254 nm wavelength. The calibration curve was linear in range of 40-10 000 ng mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…MOX was analyzed by HPLC using a previously reported method with minor modifications 48,49 . The HPLC apparatus consisted of a binary pump (Shimadzu, Burnsville, MN), a Shimadzu SPD‐20A UV–Vis detector (Shimadzu), and a prominence autosampler injector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MOX was analyzed by HPLC using a previously reported method with minor modifications 48,49 . The HPLC apparatus consisted of a binary pump (Shimadzu, Burnsville, MN), a Shimadzu SPD‐20A UV–Vis detector (Shimadzu), and a prominence autosampler injector.…”
Section: Methodsmentioning
confidence: 99%
“…MOX was analyzed by HPLC using a previously reported method with minor modifications. 48 , 49 The HPLC apparatus consisted of a binary pump (Shimadzu, Burnsville, MN), a Shimadzu SPD‐20A UV–Vis detector (Shimadzu), and a prominence autosampler injector. Briefly, a stock solution of MOX was prepared in water and/or methanol, and the stock solution was further diluted with acetonitrile to obtain a concentration range of 1–10 μg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive method validation protocol was used to establish method validation. It included linearity, range, specificity, accuracy, precision, robustness, and system suitability ICH, [16][17][18].…”
Section: Methods Validationmentioning
confidence: 99%
“…Various methods have been reported describing the assay of the fluoroquinolones and corticosteroids either singly or in combination. These methods include spectrophotometry (Abdel‐Razeq, Darwish, Zaazaa, Nasr, & Zeinab, 2015; Patel & Patel, 2013; Pradhan, Raiyani, Shah, Patel, & Upadhyay, 2015; Sversut et al, 2017), HPLC (El Gammal, El‐Wasseef, El‐Ashry, & Saadia, 2018; Gandhi, Rao, & Rao, 2016; Saad, Essam, Elzanfaly, & Amer, 2020; Sher, Fatima, Perveen, & Siddiqui, 2019; Sversut et al, 2014), thin‐layer chromatography (TLC) (Dorofeev, Konovalov, Kochin, & Arzamastsev, 2004; Musharraf, Fatima, & Sultana, 2012; Saad et al, 2020; Seid, Hymete, & Bekhit, 2012), capillary electrophoresis (Al Azzam, Saad, Adnan, & Aboul‐Enein, 2010; Alnajjar, 2013; Bourdon et al, 2013; Gallego & Arroyo, 2003; Horstkötter & Blaschke, 2001; Maher et al, 2013; Olędzka, Kowalski, Plenis, & Bączek, 2017; British Pharmacopoeia, 2013; Song, Bai, Jia, & Zhou, 2008; Suliman, Elbashir, & Schmitz, 2015; Wang et al, 2009; Zhu, Jiang, & Hu, 2002) and electrochemical methods (El‐Rahman, Lotfy, Hegazy, Rezk, & Rostom, 2015; Smajdor, Piech, & Paczosa‐Bator, 2016; Zhang, Gu, Ding, Li, & Liu, 2013; Zhang, Gu, Ding, Zhang, & Li, 2013). After a thorough investigation of literature, it was observed that no capillary electrophoretic method has been published for the simultaneous assay of the four chosen drugs.…”
Section: Introductionmentioning
confidence: 99%